An assessment into the state of transformation disclosure for the top 50 companies listed on the Johannesburg Stock Exchange - Mjali, Chuma (College of Accounting, 2020)
The main purpose of this study is to examine the current extent of transformation disclosure in the integrated reports/annual reports of the top 50 listed South African companies on the Johannesburg Securities Exchange (JSE) for the 2018 year. A longitudinal assessment to discern the developments in transformation disclosure trends over a 5-year period (2014 -2018) was also undertaken. Transformation for purposes of this study refers to transformation of the workplace “to be truly non-racial and non-sexist within companies”. Transformation is very topical in South Africa bearing in mind the historical injustices of the past and thus the need for redress. Disclosure relating to transformation is argued to be a pivotal contributing instrument that could empower stakeholders towards holding companies accountable. The specified transformation disclosure is required by the Employment Equity Act and is considered to be mandatory. The transformation disclosure reported by companies within their annual reports/integrated reports was thus critically scrutinised by application of a scoring technique relating to a closed list of 15 variables selected. Results showed that disclosure relating to the transformation variables was low overall despite there being a statutory requirement, with the highest scores recorded around the corporate social responsibility variable. The stunted level of transformation disclosure has wider implications for users of these reports and their ability to be afforded the opportunity to facilitate action and thus exercise accountability in relation to these companies.